Serum 25-Hydroxyvitamin D Levels and Disease Activity in Patients with Systemic Lupus Erythematosus: An Exploratory Study in Western Mexico - Daniela Deossa-Piedrahita; Berenice Vicente-Hernández; Sol Ramírez-Ochoa; Mauricio Alfredo Ambriz-Alarcón; Gabino Cervantes-Pérez; Gabino Cervantes-Guevara; Alejandro González-Ojeda; Clotilde Fuentes-Orozco; Francisco Javier Hernández-Mora; Luis Asdruval Zepeda-Gutiérrez; Jorge Isaac Michel-González; Janet Cristina Vázquez-Beltrán; et al. (Diseases)
Background and objectives: The correlation between diminished 25-hydroxyvitamin D (25-(OH)D) concentrations and heightened disease activity in systemic lupus erythematosus (SLE) patients remains contentious, as clinical studies have yielded conflicting outcomes—some propose a potential link, while others assert no relationship exists. Nonetheless, all studies report a significant prevalence of low 25-(OH)D levels among SLE patients. This study aimed to assess the frequency of low serum levels of 25-(OH)D in Mexican patients with SLE and to evaluate the correlation between 25-(OH)D deficiency or insufficiency and disease activity levels. Materials and Methods: This retrospective analysis comprised patients admitted to our hospital from November 2022 to October 2023, diagnosed with SLE, and had their serum 25-(OH)D levels tested upon admission. The frequency of low levels of 25-(OH)D was assessed, and clinical and demographic data were gathered to examine potential causes linked to 25-(OH)D deficiency or insufficiency. Results: A total of 61 patients were included, and 87% (n = 53) had low serum 25-(OH)D levels. Patients with 25-(OH)D deficiency (n = 21) were significantly younger (mean 23 vs. 39 years, p = 0.04) and had higher protein levels in 24 h urine protein (1.8 vs. 1.1 g/24 h, p = 0.006) than patients who presented only 25-(OH)D insufficiency, without significant differences in other indicators of disease activity. Conclusions: In this investigation, patients with SLE exhibited a high frequency of low serum levels of 25-(OH)D, consistent with existing literature; however, no significant correlations were identified between 25-(OH)D levels and indicators of disease activity. These findings require validation in subsequent research.